Understand Consumer Perception of Waiting Time in Services Urban Developing: A Study in Cirebon City, Indonesia - Hindam Syarifudin; Wachdijono Wachdijono (Yayasan Adra Karima Hubbi, 2026)
Service lead time plays an important role in shaping consumer perception of overall service quality. If the service wait time is perceived as long, consumers will get bored and leave, but if it is perceived as quick, they will be happy and make a purchase again. This study aims to determine the index of consumer perception of service waiting time and the scores for each indicator in univariate analysis. The research was conducted at the Gacoan Noodle Restaurant in Cirebon City for three months (December 2025-February 2026). The research design uses quantitative descriptive and survey techniques. The sample consisted of 60 respondents, and the sampling technique was accidental. The indicator measurement uses the Likert Scale, and the data analysis is univariate, using a mathematical formula. The results showed that the consumer perception index was 69.7% (service waiting time is fast). The highest indicator score was 77.2% clarity and certainty of service (maintained), and the lowest indicator score was 65.7% (improved). The gap in this study is an empirical and methodological one, so that the results of this research contribute theoretically to the development of consumer behavior theory and methodology. Technically, it contributes to the business actors of Mie Gacoan Restaurant in Cirebon City in order to achieve a competitive advantage.